Heuristic approach to minimise the energy consumption of sensors in cloud environment for wireless body area network applications. (5th May 2020) - Kumaresan, P.; Prabukumar, Manoharan; Subha, S.
The wireless sensor networks are single user centric and end users who do not own sensors are unable to have access to any wireless network specific application. This sensor cloud is a new paradigm to manage the physical sensors which are deployed in any WSN application. Existing research work on sensor cloud is limited to guaranteeing minimal energy consumption. In this paper, a novel mathematical model based on virtual sensor grouping is proposed to minimise the cumulative energy consumption of sensors in cloud environment. Energy consumption of non-virtual sensor with virtual sensor group for two different applications is compared and the results are shown. Further the proposed sensor cloud infrastructure with power model is compared with traditional WSN with respect to energy efficiency, throughput and performance with quick synchronisation time for random run trials and results were found to be better than the conventional WSN.